Different Patterns of Attentional Bias in Subjects with Spider Phobia: A Dot Probe Task using Virtual Reality Environment - Alvaro Frías (Archives of Depression and Anxiety - Peertechz Publications, 2015)
Background: Cognitive theories posit that all animal phobics develop a hypervigilance- avoidance  attentional  pattern  when  coping  with  threat. However,  empirical research has failed to obtain consistent results. We aimed at addressing this issue by diminishing the methodological flaws that hinder the internal and ecological validity of previous studies. Methods: In this research, 34 spider fearful and 33 non-fearful participants completed a probe dot task using virtual reality environments. A subjective threshold for each participant was established. Position of the probe (low vs. up) and interval between trials (regular vs. irregular) were controlled. Results: Compared to non-fearful individuals, spider phobics showed preconscious attentional bias  towards threat in unexpected (low  and  irregular) trials.  Moreover, phobics tended to display conscious attentional bias away from threat in unexpected (irregular) trials. Severity of fear did not correlate with attentional bias. Limitations: We did not use eye movement tracking as well as potential biomarkers for attentional bias (e.g., event-related potentials). The risk of type-I error cannot be ruled out. Conclusions: These findings partly support the hyper vigilance-avoidance pattern by considering some contextual factors that may enhance uncertainty in phobics. The alleged role of attentional bias in phobias is also questioned.